A Closer Look on the Oblique Plural of Words Terminating in the Letter Yey: Pashto Grammatical Case - Anwar Wafi Hayat (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
This article studies the grammatical case of the Pashto language, with its focus on the oblique plural case of words terminating in different types of the letter ی /Yey/, where such cases of words are formed by replacing its various types with either و /waaw/, or یو /yow/. A summative approach to qualitative content analysis was used to analyse the data. The current grammatical rules of such words were studied in-depth but did not include rules where the oblique plurals thereof end in یانو /yaanow/. The study aimed to explore the problems of related grammatical rules and the trend of making such plurals where, except for the long Yey ې, the writers tend to replace most types of the letter Yey with یو /yow/. The paper also investigates what type of the letter Yey ی must be replaced with و and what type with یو, and whether replacing every type thereof with و or replacing all with یو will create ambiguity concerning the meaning of words used in their oblique plural cases. The study found that replacing all or most types of this letter with و or replacing all or most types thereof with یو results in ambiguity leading to the wrong meaning of words. In addition, findings hereof showed that only the feminine Yey ۍ should be replaced with یو. A fresh approach to making the oblique plural cases of such words has been introduced, and new rules are proposed, thereby facilitating writers in figuring out the correct oblique plural case of words. This study is the first attempt at unearthing the problems associated with the oblique plurals, as prior to this, no such study has been done in regard thereto.